India : some aspects of economic and social development - Dev, S.Mahendra (ed.) (New Delhi, 2008)
Agricultural issues, governance and growth, and universities are just a few of the topics covered by a plethora of well-known, international scholars in this volume on the diverse and growing country of India. Contributor essays are organized into five main categories: social issues, which include higher education and human development; a comparison of India and China development paths; a comparison of Indian fiscal federalism; employment and poverty; and recent issues in agriculture.
Keywords: India - Economic policy